Paradigm Shift in the Role of Independent Directors in Indian Public Sector Undertakings using Data Mining Method (International Journal of Advanced Research in Science, Management and Technology, 2021)
The objective of this paper is to identify the relationship between Independent Directors and Public Sector Undertakings (PSU) financial performance by data mining method. We have taken the dependent variables, Altman Z-Score ratio to measure the Indian Public Sector Undertakings (PSU) financial performance. The independent variable is response of Independent Directors of Public Sector Undertaking (PSU) through our questionnaire. We used Pearson and Spearmen correlation to find the relationship between the two variables. We found that there is a ‘weak correlation’ among the variables, before the amendment of Companies Act, 2013 and “strong correlation” after the amendment of Companies Act, 2013. So we can say that there exists a paradigm shift in the role of Independent Directors post the legislative changes.
Keywords: Independent Director, Public Sector Undertaking (PSU), Association Rules, Data Mining, Financial Performance.